Longitudinal evolution of magnetization of ferromagnets following ultrafast demagnetization: role of finite size and shape of demagnetized region - Yastremsky, I.A. (Condensed Matter Physics, 2014)
A dependence of a relaxation rate on the shape of the demagnetized region for a longitudinal evolution of total magnetization to its equilibrium value following the ultrafast demagnetization is demonstrated. This shape-dependence is caused by a motion of the wave front inside the demagnetized region. The contribution of the wave front for spherically symmetric shape of the demagnetized region is up to 3 times and for cylindrically symmetric shape up to 2 times stronger than for one dimensional demagnetized region. This effect can be observed after the demagnetization by a tightly focused femtosecond laser pulse. Розглядається поведiнка системи взаємодiючих частинок в областi температур нижче критичної точки
T É Tc. Завершується розрахунок великої статистичної суми, початий у попереднiх роботах у методi колективних змiнних. За базову густину мiри береться четвiрний (а не Гаусовий) розподiл. Описанi подiї
пов’язанi з фазовим переходом 1-го роду, що вiдбуваються в результатi iзотермiчного квазiстатичного
стиснення газу. Видiлена лiнiя µ
∗(η) = 0, на якiй у газовiй фазi пiд дiєю тиску виникає крапля рiдини. Має
мiсце рiвнiсть хiмiчних потенцiалiв газової i рiдкої (у краплi) фаз; знайдено величину поверхневої енергiї краплi, розраховано скриту роботу конденсацiї, визначено скачок густини, написано рiвняння стану.
Робота становить певну кiнцеву стадiю дослiджень в областi температур i густин, що включає у собi критичну точку рiдина–газ.